2013
DOI: 10.1007/s40196-013-0025-4
|View full text |Cite
|
Sign up to set email alerts
|

The information content of implied volatility index (India VIX)

Abstract: This paper examines the predictive ability of India VIX as the best forecast of realized return volatility. This study takes into account the implied volatility index (India VIX), also known as the investors fear gauge index. We have employed OLS, 2SLS procedure and quantile regression to study the predictive power of implied volatility index. Empirical results show that India VIX is the best estimate of future realized return volatility. The Hausman specification test analyzes that implied volatility is measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 46 publications
0
15
1
Order By: Relevance
“…However, the major findings of the study suggests that investors need not to consider the scheduled macroeconomic announcement except MCIR meeting day and one day after in the valuation of options pricing or financial planning due to the inefficiency of the Indian options market. These results are contradictory with the findings of Shaikh and Padhi [13] in the Indian context. The study can be extended in terms of response of India VIX for the economic news of Europe, US and other emerging economies.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…However, the major findings of the study suggests that investors need not to consider the scheduled macroeconomic announcement except MCIR meeting day and one day after in the valuation of options pricing or financial planning due to the inefficiency of the Indian options market. These results are contradictory with the findings of Shaikh and Padhi [13] in the Indian context. The study can be extended in terms of response of India VIX for the economic news of Europe, US and other emerging economies.…”
Section: Discussioncontrasting
confidence: 99%
“…To the best of knowledge, the Shaikh and Padhi [13] is the only study attempted to investigate the response of Implied Volatility Index towards the scheduled macroeconomic announcements in the Indian context. Using the Ordinary Least Squares (OLS) and Generalised Autoregressive Conditional Heteroscedasticity (GARCH) models, they found that IVIX rises significantly prior to the scheduled announcement and remains more stable on the new releases.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the studies in the context of Indian stock market are found to be meager. To the best of knowledge, Shaikh and Padhi [19] is the only study attempted to investigate the asymmetric contemporaneous linkage between India VIX and NIFTY Index and they established linkage is negative and asymmetric. In another study, Shaikh and Padhi [19] investigated the behaviour of India VIX during, before and after the scheduled macroeconomic news release and they implicitly assumed the symmetric behaviour of market reactions towards positive and negative shocks.…”
Section: Review Of Literaturementioning
confidence: 99%